Efficacy of organic and inorganic treatments against Alternaria leaf spot disease of Conocarpus erectus L. in Iraq - Abdul-Karim, Eman k.; Ali, Haneen Abd-Alhaleem; Kareem, Tariq A. (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2026)
Severe leaf spot disease has recently been observed on Conocarpus erectus (buttonwood) trees in Iraq, with artificial inoculation resulting in a disease severity of 91.6%. Morphological, microscopic, and molecular analyses using ITS1/ITS4 primers identified Alternaria alternata as the causal agent. Two isolates (Alt.1IQ and Alt.2IQ; GenBank accession numbers OM994386 and OM994387) exhibited 98.05–100% sequence similarity with previously reported Iraqi isolates. In vitro antifungal assays demonstrated that magnesium sulphate, sodium bicarbonate, and neem oil at a concentration of 0.4% inhibited fungal growth by 57.63%, 55.62%, and 50.80%, respectively. Laboratory leaf assays revealed that all tested treatments at 0.2–0.4% completely suppressed fungal development, resulting in 0% affected leaf area compared with 31.96% in the untreated control. Nursery trials showed that neem oil and sodium bicarbonate were the most effective treatments, reducing disease severity to 8.3–16.6% and 8.3–25.0%, respectively, while magnesium sulphate achieved a moderate reduction (24.33–25.0%. The chemical fungicide Coastine 38WG completely prevented disease development (0% severity), whereas untreated seedlings exhibited 91.6% disease severity. Overall, neem oil and sodium bicarbonate at 0.4% emerged as promising eco-friendly alternatives for managing A. alternata –induced leaf spot disease in Conocarpus seedlings. These findings support their potential incorporation into sustainable and integrated disease management strategies aimed at reducing reliance on synthetic fungicides.